New generation storage security - Seet, Kah Wee (2014)
As the computer and network evolved and linked with each other, so as the threats of security risks as each breach into the network may incur heavy losses. However implementing security on a efficient network will slow the network and its performance which may also incur losses. Therefore there is a need to implement next generation storage security.